Human Capital Disclosure: A Review Article - Uddin, Humayun Fareed; Salman, Syed Muhammad; Hassan, Muhammad; Latif, Muhammad Rizwan; Aziz, Atif (iRASD Journal of Economics, 2023)
This article aims to provide deep insight towards the basic understanding of intellectual capital disclosure specifically from the perspective of human capital disclosure. This study reviews the article and primarily focuses on a systematic review of past studies on human capital disclosure. There is a perception among potential investors that intellectual capital information shared by corporate companies is diverse in characteristics. In many developing economies, the government heavily influences corporate culture companies to abide by accounting and corporate practices in the modern world. However, from the investor perspective, the intellectual capital information tends to be net investee; therefore, their emphasis is mostly on corporate information supply. This article summarizes corporate information disclosure and provides the connection between the social, corporate and accounting practices in developing economies.